Effect of arbuscular mycorrhiza and rhizobium on physiology and yield of peanut under drought conditions - Aninbon, Chorkaew; Teamkao, Pattrarat; Buram, Kiattisak; Kaewnoo, Tipawan; Ruttanaprasert, Ruttanachira; Janket, Anon; Mon, Yi Yi; Kaewtaphan, Phissanu (Frontiers in Plant Science, 2024)
The study aimed to investigate the effects of arbuscular mycorrhizal fungi (AMF), rhizobium (Rhi), and their combinations on phenolic content, proline content, growth and yield of peanut under different soil water regimes. The pot experiments were carried out for two growing seasons under greenhouse conditions and designed based on a 2×3 factorial in randomized complete block design (RCBD) with four replications. Factor A comprised of two soil water regimes: field capacity (FC) and 1/3 available soil water (1/3 AW), whereas factor B included three different types of microorganisms: (i) uninoculated control, (ii) arbuscular mycorrhiza (AMF), and (iii) a combination of AMF and rhizobium (Rhi) inoculations. Data were collected for growth, proline content, phenolic content, yield and yield components. Drought stress significantly reduced in relative water content, leaf area, biomass, yield, and yield components of peanut, whereas leaf phenolic content was increased under drought stress. Higher pod dry weight was achieved under FC conditions (28.87 grams per plant), and it was reduced to 16.06 grams per plant under 1/3 FC. Interestingly, the AMF+Rhi synergistically increased leaf area compared to nonincubated peanut under 1/3 FC conditions. AMF-inoculated peanut tended to increase biomass, while the combination of AMF+Rhi tended to have higher yield components compared to uninoculated control, especially for the weight of 100 seeds.